sIgG4 and Other Tolerance Predictors at Food Allergy in Early Age Children - I. A. Deev; M. I. Petrovskaya; L. S. Namazova-Baranova; S. G. Makarova; I. V. Zubkova; N. A. Mayansky (Union of pediatricians of Russia, 2015)
Despite modern achievements in child allergology, the question of evaluating tolerance formation and defining the safest time for expanding the child's ration after an eliminatory diet remains open. This article contains the results of the authors' own investigation concerning the practical meaning of specific immunoglobulins (sIg) class G4 as tolerance formation markers at food allergies in children. Thus, it has been found that high levels of sIgG4 are not only a favourable prognostic factor for light manifestations of food allergy, but also an index of a tolerance formation. The prevalence of high food allergy sIgG4 was statistically significantly higher in early age children from the comparison group than in patients with food allergy. Thus the authors suggest that the production of sIgG4 is a normal physiological process which hinders the development of hypersensitivity, while high levels of sIgG4 are evidence for the child's immune system "contacting" this or that product. Clinical tolerance formation predictors define lighter clinical manifestations of food allergies, a non IgE-mediated form of food allergy and the retention of breastfeeding.